Treatment of hydatidiform mole suspected to COVID 19 - Fatemeh Azarkish; Saeedeh Rigiyousefabadi; Roksana Janghorban; Mohammadmehran Aminifard; Shirin Bozorgzadeh; Mahya Zahirnia; Mansooreh Sadat Golmohammadi; Elahe Mirtalaie; Arezoo Pirak; Zahra Atarodi Kashani (Advanced Biomedical Research, 2022)
The aim of this study was to report a case of the treatment of hydatidiform mole in Coronavirus pandemic in Iranshahr. A 17-year-old primiparous woman with gestational age of 14 weeks presented with unilateral leg swelling and sudden abdominal distension beginning in the night before referring to the health center. In the abdominal examination of the patient by a healthcare provider, the baby's heartbeat was not heard and a mismatch was observed between gestational age and fundal height, which corresponded to approximately 24 weeks of gestation. She was conscious and pale with hematuria and uterine contractions. After inserting two IV lines, the patient immediately underwent monitoring and was visited by a gynecologist. Complete molar pregnancy was diagnosed with an enlarged heterogeneous uterus 180 cm × 90 cm in size and containing 170 mm × 80 mm cysts. The treatment began with vancomycin AMP, hydrocortisone AMP, oseltamivir CAP 75 mg, kaletra CAP 200 mg, and meropenem AMP.